PENATAAN ELEMEN SIRKULASI VERTIKAL PADA GEDUNG UNPAR JL.MERDEKA no.30 BANDUNG MELALUI PENDEKATAN SPACE SYNTAX DAN KRITERIA HERITAGE - Rachadian Hadiwibowo (Ide dan Dialog Desain Indonesia (Idealog), 2019)
There is a need for easier vertical circulation facilities, especially given the need for people with disabilities and parents in historic buildings, especially in buildings that still function as public buildings to date. This is because in general these buildings use stairs as a means of vertical circulation while the activities inside have increased so that more efficient vertical circulation is needed such as elevators. The problem is how to determine the placement of vertical circulation facilities in historical buildings, which sometimes do not accommodate the placement of new vertical circulation facilities and placement should be in locations that are easily accessible and seen by users but at the same time also pay attention to the rules of buildingconservation rules. This study aims to show the use of the Space Syntaxmethod can be used in conjunction with the conservation study of historic buildings to determine the placement of vertical circulation facilities in buildings as a space study tool that will determine the location of placement in terms of accesibility and connectedness of space which will then be used to determine placement new elements in the building while paying attention to the principles of cultural heritage conservation. The study used quantitative methods of ekseprimental simulation with the use of Depthmap's computer program as a tool for analysis of simulation of the Space Syntaxmethod, supported by heritage provisions as a guide to limits of changes allowed in cultural heritage buildings. The results showed that the use of Space Syntaxcan be used in conjunction with the analysis of building conservation to determine elevator placement in locations that pay attention to the study of ease of achievement and observation of usersbut still pay attention to the influence of the placement on historical and architectural elements of the building shown in the case study of the UNPAR building Jl.merdeka no.30 Bandung.